2018
DOI: 10.1159/000487196
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Contralateral Operation after Initial Pyeloplasty in Children with Antenatally Detected Bilateral Hydronephrosis Due to Ureteropelvic Junction Obstruction

Abstract: Objectives: This study was performed to analyze the predictive factors of a contralateral operation after initial pyeloplasty in patients with antenatally detected bilateral ureteropelvic junction obstruction. Methods: Patients with prenatally diagnosed bilateral ureteropelvic junction obstruction who underwent initial pyeloplasty (aged <12 months at initial pyeloplasty) were offered to participate in the study. Patients were recruited from January 2012 to December 2015. The anteroposterior renal pelvic diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…12,13 Parameters from scintigraphy, diuresis renography and ultrasonography, like differential renal function, calyceal dilatation and calyceal dilatation/ parenchymal thickness ratio have been shown to guide management and assess outcome. 14,15 These assessment tools are more useful for cases seen early and in whom upper urinary tract damage can be minmised. [16][17][18] Detailed preoperative evaluation of children diagnosed early is able to predict those that will require surgery and give guidance to management.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Parameters from scintigraphy, diuresis renography and ultrasonography, like differential renal function, calyceal dilatation and calyceal dilatation/ parenchymal thickness ratio have been shown to guide management and assess outcome. 14,15 These assessment tools are more useful for cases seen early and in whom upper urinary tract damage can be minmised. [16][17][18] Detailed preoperative evaluation of children diagnosed early is able to predict those that will require surgery and give guidance to management.…”
Section: Discussionmentioning
confidence: 99%
“…Probability of postnatal surgery was 15% in cases where renal pelvis AP diameter was ≥15 mm (35). When calyx dilatation is ≥10 mm, spontaneous resolution is 37%, the possibility of persistence is 29% and the surgical requirement is around 33% (35). However, in cases where calyx dilatation was <5 mm and AP diameter was <10 mm, 90-100% regression was reported, and there is virtually no need for surgery (0-3.7%) (35).…”
Section: Parameters Determining Poor Prognosis In Prenatal Upjhnmentioning
confidence: 99%
“…Jiang et al reported a spontaneous regression rate of 61%, and persistence rate of 23% in cases diagnosed with antenatal bilateral UPJHN (35). Probability of postnatal surgery was 15% in cases where renal pelvis AP diameter was ≥15 mm (35).…”
Section: Parameters Determining Poor Prognosis In Prenatal Upjhnmentioning
confidence: 99%
See 2 more Smart Citations